Allogeneic transplant for chronic myeloid leukemia in 2010 - Radich, Jerald P. (SAGE Publications, 2010)
Tyrosine kinase inhibitor (TKI) therapy has revolutionized the therapy of chronic myeloid Leukemia (CML). Thus, while in the near past allogeneic transplantation was the curative option for CML, imatinib, nilotinib, and dasatinib have pushed transplantation to the role of salvage therapy in CML. Still, TKI therapy still fails some patients, and so the clinical challenge is to integrate transplantation in a safe and sane manner. This manuscript reviews the data on the variables that have an influence on outcome following transplantation, and discusses the variables to consider in determining who and when patients should receive transplantation.